2017
DOI: 10.3389/fimmu.2017.00991
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Infection Differentially Regulates the Phenotype and Function of γδ T Cells in HIV-1-Infected Patients Depends on the HIV-1 Disease Stage

Abstract: A rapidly escalating outbreak of syphilis infection has been affected men who have sex with men, particularly those with HIV-1 infection. γδ T cells are unconventional immune cells with two main subsets, Vδ1 T cells and Vδ2 T cells, which possess a combination of innate and adaptive immune features allowing them against HIV-1. However, whether syphilis infection affects the phenotype and function of γδ T cells in HIV-1-infected patients remains unclear, especially in acute HIV-1 infection (AHI). In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 70 publications
(73 reference statements)
2
18
0
Order By: Relevance
“…A subset of γδ T cells have been shown to serve as reservoir for HIV infection . Finding in this study that IL‐17 levels were higher among CHIV persons compared to EHIV is similar to reports from previous studies . IL‐17 production has previously been largely attributed to γδ, DNT and neutrophils.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A subset of γδ T cells have been shown to serve as reservoir for HIV infection . Finding in this study that IL‐17 levels were higher among CHIV persons compared to EHIV is similar to reports from previous studies . IL‐17 production has previously been largely attributed to γδ, DNT and neutrophils.…”
Section: Discussionsupporting
confidence: 90%
“…IL‐17 production has previously been largely attributed to γδ, DNT and neutrophils. This IL‐17/neutrophil/ γδ T cell production axis has been shown to be critical to HIV‐1 disease progression . Data from this study showed that high HIV‐1 RNA viral load as well as urea levels may impact negatively on the IL‐17/neutrophil/ γδ T cells axis thereby limiting their activation during the early stages of infection.…”
Section: Discussionmentioning
confidence: 80%
“…The destructive impact of HIV infection on Vd2 T cells stands in direct contrast to the observed expansion of peripheral Vd1 T cells, 32,[36][37][38] which occurs rapidly during acute infection (and prior to HIV seroconversion 38 ). Several studies have confirmed that the relative enrichment of Vd1 cells as a proportion of the total cd T-cell population is also reflected as an increase in absolute Vd1 33,[38][39][40][41][42][43][44][45][46][47] ) T-cell count in the periphery. Similar to Vd2 cells, Vd1 cells are significantly more activated in HIV-infected subjects compared with controls.…”
Section: Peripheral Vd1 T Cellsmentioning
confidence: 99%
“…10 However, they have been observed to expand in the blood in patients with cytomegalovirus infection, CD4 T-cell deficiency and B-cell leukaemia. 29 Multiple reports have since described an inversion of the typical Vd2:Vd1 T-cell ratio in the peripheral blood of HIV-infected/AIDS patients, [30][31][32][33] which was quickly determined to represent an increase in Vd1 T-cell frequency 30,[32][33][34][35][36][37][38][39][40][41][42][43][44] and a depletion of Vd2Vc9 T cells. In 2017, an estimated 36.9 million people were currently infected with the virus of which 1.8 million were children under the age of 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation